Introduction to the First Spanish Edition of Vera Zasulich’s "The Terrorist Tendency in Russia" (December 1902) - Gaido, Daniel; Jozami, Maximiliano (Revista de Historia Social y de las Mentalidades, 2024)
We present to the reader a critical edition of Vera Zasulich’s article on the russian Socialist Revolutionary Party, written shortly after its creation and hitherto untranslated to spanish, originally published in two installments in the theoretical journal of the Social Democratic Party of Germany, die neue zeit, edited by Karl Kautsky. Zasulich’s article is preceded by the editors’ introduction, which contextualizes the document and draws a parallel between the russian narodniki (populists) and eserists (socialist revolutionaries), on the one hand, and latin american foquism in the 1960s and 1970s on the other hand. The first part shows that the ideas contained in Lenin’s book what is to be done? (published in march 1902) were not some new form of party organisation concocted by Lenin but a reflection of the ideas of the whole group that edited the journal iskra about the organisational needs of the Russian Social Democratic Labour Party (RSDLP). The second part of the article shows that the russian marxists’ struggle was directed against the revival, not only of the tactics of individual terrorism and armed propaganda as the title indicates, but also against the old “peasant way to socialismË® of the populists in a new guise.